DISIPLIN KERJA AUDITOR MEMODERASI PENGARUH INDEPENDENSI DAN AKUNTABILITAS AUDITOR PADA KUALITAS AUDIT - Junanta, Ida Bagus Gede Krisna; Badera, I Dewa Nyoman (E-Jurnal Akuntansi, 2016)
This study aims to determine the effect of independence and accountability on the audit's quality and also to determine whether the work discipline moderates the influence on the independence and accountability of audit's quality. The study was conducted at KAP listed in the IAPI region of Bali in 2015. The sample was selected using purposive sampling technique. Data obtained by questionnaires to the auditors and the analysis technique used are multiple regressions and MRA. Result of the research showed testing instruments and classic assumptions are met. Based on the analysis, it is known that the independence and accountability effects positively the quality of an audit. Work discipline of an auditor aren't able to moderate the influence on the independence of an audit's quality, but the auditor's discipline of work are able to moderate the influence of auditors accountability on audit's quality
Keywords: Auditor Independence, Auditor Accountability, Discipline of Work, Audit Quality